2016
DOI: 10.3390/met6100232
|View full text |Cite
|
Sign up to set email alerts
|

Erosion Behaviour of API X100 Pipeline Steel at Various Impact Angles and Particle Speeds

Abstract: Abstract:Erosion is the gradual removal of material due to solid particle impingement and results in a failure of pipeline materials. In this study, a series of erosion tests were carried out to investigate the influence of particle speed and impact angle on the erosion mechanism of API X100 pipeline steel. A dry erosion machine was used as the test equipment, while the particle speed ranged from 20 to 80 m/s and impact angles of 30 • and 90 • were used as test parameters. The eroded API X100 steel surface was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…The second possible reason is that Figure 6 displays the erosion rate of Al x CoCrFeNiTi 0.5 HEA coatings and Cr16 alloy as a function of impingement angle after erosion for 30 min. The Al 1.0 HEA coating and Cr16 alloy showed the maximum erosion rate at 45 • , then the erosion rate decreasing gradually with the impingement angle, which is consistent with the theory of the ductile mode of erosion behavior [19,20]. The erosion rate of the Al 1.5 HEA coating approached a maximum at 60 • and then decreased at 90 • .…”
Section: Microstructure and Xrd Analysissupporting
confidence: 73%
“…The second possible reason is that Figure 6 displays the erosion rate of Al x CoCrFeNiTi 0.5 HEA coatings and Cr16 alloy as a function of impingement angle after erosion for 30 min. The Al 1.0 HEA coating and Cr16 alloy showed the maximum erosion rate at 45 • , then the erosion rate decreasing gradually with the impingement angle, which is consistent with the theory of the ductile mode of erosion behavior [19,20]. The erosion rate of the Al 1.5 HEA coating approached a maximum at 60 • and then decreased at 90 • .…”
Section: Microstructure and Xrd Analysissupporting
confidence: 73%
“…Experimental study of these parameters on erosion process is one of the effective ways to analyse the erosion mechanism. Okonkwo et al [5] studied the erosion behaviour of pipeline steel at particle speed ranging 20-80 m/s and impact angle at 30°and 90°. The authors have found that ploughing mechanism is dominated at 90°i mpact angle while cutting at 30°impact angle.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical composition of the API X100 steel used in the present study was determined by an optical emission (OE) spectrometer, ARL 3460 (Thermo Fisher Scientific SARL, Ecublens, Switzerland). The sample preparation procedure and the chemical composition are detailed elsewhere [28,29].…”
Section: Materials Preparationmentioning
confidence: 99%
“…Switzerland). The sample preparation procedure and the chemical composition are detailed elsewhere [28,29].…”
Section: Electrochemical Measurement Setupmentioning
confidence: 99%